Towards micro-imaging with dissolution dynamic nuclear polarisation - Gaunt, Adam P. (2018)
Nuclear magnetic resonance (NMR) of small samples and nuclei with a low gyromagnetic ratio is intrinsically insensitive due to the received signal dependence on Boltzmann's statistics. This insensitivity can be partially overcome through the application of hyper polarisation techniques such as Dissolution Dynamic Nuclear Polarisation (D-DNP). It is hoped that the hyper polarised 13C signal received from labelled small molecules could facilitate imaging of metabolic and transporter processes in biological systems. In order to realise this, appropriate molecules and experimental hardware must be used. A detailed description of the experimental set-up used for carrying out DDNP is given and the system is characterised. the advantageous use of a dual iso-centre magnet system is elucidated with optimisation of acquisition of fast relaxing molecules. such a system allows for interrogation of processes with short relaxation times, not possible with traditional, stand-alone polarisers.